2012
DOI: 10.1007/s00792-012-0447-y
|View full text |Cite
|
Sign up to set email alerts
|

Three nth homologs are all required for efficient repair of spontaneous DNA damage in Deinococcus radiodurans

Abstract: Deinococcus radiodurans is a bacterium that can survive extreme DNA damage. To understand the role of endonuclease III (Nth) in oxidative repair and mutagenesis, we constructed nth single, double and triple mutants. The nth mutants showed no significant difference with wild type in both IR resistance and H(2)O(2) resistance. We characterized these strains with regard to mutation rates and mutation spectrum using the rpoB/Rif(r) system. The Rif(r) frequency of mutant MK1 (△dr0289) was twofold higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…The nth single, double and triple mutants are as resistant to IR and H 2 O 2 as the wild type, but each single mutant shows slightly elevated levels of spontaneous mutation (Hua et al. 2012). In vitro , enzymatic activity has been detected for DR_0289 and DR_2438, but so far not for DR_0928 (Sarre et al.…”
Section: Dna Repair In Deinococcusmentioning
confidence: 99%
“…The nth single, double and triple mutants are as resistant to IR and H 2 O 2 as the wild type, but each single mutant shows slightly elevated levels of spontaneous mutation (Hua et al. 2012). In vitro , enzymatic activity has been detected for DR_0289 and DR_2438, but so far not for DR_0928 (Sarre et al.…”
Section: Dna Repair In Deinococcusmentioning
confidence: 99%
“…The total number of colony-forming units (CFU) was determined by plating serial dilutions on LB plates. The frequencies of mutations conferring resistance to Rif were determined by dividing the median number of mutants by the average number of cells [26]. For mutation rates, the maximum-likelihood estimator applying the newton.…”
Section: Measurement Of Mutation Frequency and Mutation Rate In Rif Rmentioning
confidence: 99%
“…The PCR products were purified and sequenced by Biosune biological company (Hangzhou, China). The sequences and trace data were transferred to the SEQMAN program (DNASTAR), which was used for sequence assembly and SNP detection [26].…”
Section: Dna Isolation and Rpob Sequencing Of Rif R Mutantsmentioning
confidence: 99%
“…Similarly, homozygous Arabidopsis thaliana arp −/− (AP endonuclease homologous gene) mutant exhibited no sensitivity to H 2 O 2 , but high sensitivity to tert-butyl hydroperoxide, suggesting that ARP is a major plant AP endonuclease that removes the special types of oxidative DNA base damage (Akishev et al, 2016). Meanwhile, the D. radiodurans polX mutant and endonuclease III (nth) mutants showed no significant difference from wild type in H 2 O 2 stress resistance (Khairnar and Misra, 2009;Hua et al, 2012). It has also been shown that mutation of both ttendolVI and ttpolX resulted in a significant decline in activity following exposure to H 2 O 2 in Thermus thermophilus (Nakane et al, 2012).…”
Section: Discussionmentioning
confidence: 99%